Forgotten Nature? Experiences with and Knowledge of Nature Among Schoolchildren: A Pilot Study in Central Switzerland - Jürgen Kühnis; Désirée Fahrni (University of Maribor Press, 2021)
This pilot study investigates the extent of familiarity among primary school children (6th grades, n = 142, 55.6 % boys) with common local animal and plant species and whether this knowledge differs depending on selected context variables. As the analysis shows, nature is of great importance, and most children already have gathered some basic experience of nature. On average, they correctly identified 51.2 % of the animals and 36.2 % of the plants, but there were obvious gaps in their knowledge. The present results showed a clear connection between the knowledge of native animal and plant species depending on the child's nationality, whether they have a garden at home and how their parents stimulate their interest in nature.